Cultural and Religious Perspectives on Zakat and Poverty Alleviation: Christian Perspective - Peter, Isaac (International Journal of Zakat, 2024)
This paper explores the cultural and religious perspectives on zakat and poverty alleviation through a comparative lens, specifically focusing on the Christian approach to economic justice and poverty reduction. While zakat in Islam is a formalized, mandatory almsgiving practice integral to financial equity, Christianity approaches poverty alleviation through voluntary giving, communal support, and advocacy for social justice. Drawing from biblical teachings, Christian traditions emphasize compassion, charity, and systemic transformation to reduce poverty and uplift the marginalized. Key themes include the moral duty of generosity, rooted in Jesus' teachings on caring for the poor, as well as church-led efforts in charity and social reform, which mirror the principles of zakat but are applied flexibly within Christian practice. The paper underscores that while both zakat and Christian charity aim at poverty alleviation, they differ in structure and approach, reflecting unique theological foundations yet converging on the shared objective of fostering social welfare and economic justice. Through examining these frameworks, the paper highlights how religious values shape attitudes and actions towards poverty, emphasizing a holistic approach to human dignity, economic sustainability, and community support.